PEMAKNAAN SIMBOL PADA INTERAKSI SOSIAL MASYARAKAT ISLAM – HINDU DI KOTA MATARAM NUSA TENGGARA BARAT - Basuki Basuki (Jurnal Ilmu Komunikasi, 2009)
Religion as a doctrine/ideology has formed as a belief toward to the existence of the God almighty and culture as the implementation of human relationship among human and the God. Different understanding of God’s essence has created some kinds of religions and beliefs. It causes difference of culture (value, norm, behavior) among religions adherer. Even the differences can be opposite each other. As the example, Moslem believes in monotheism and Hindu believes polytheism. This research purpose is examining how do the societies giving meaning of symbolic in having the interaction between Hindu and Moslem community in Mataram City. From the research it can be examined that of adhering a religion (both Hindu and Islam) basically because following their ancestor. They have no courage to challenge what their ancestor have line up. They have no courage to ask the reason even to discuss it to interpret the meaning of the symbols. Their fear to insult others becomes the obstacle to them. They use their own point of view and some general information that they have got to interpret another religion. Nevertheless, social interaction can happen well. In this case, Moslem community is much more closed than Hindu.